“Efectos de la aplicación de tres fuentes nitrogenadas y dos potásicas, sobre el rendimiento del cultivo de maíz (Zea mays L.), en la zona de Babahoyo” - Benítez Jiménez, Pamela Gyvanna (2018)
VII. SUMMARY The present experimental work was carried out in the land of the farm that is located in the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located in Km. 7.5 of the Babahoyo-Montalvo road, with geographical coordinates (UTM) X; 6631487, Y; 979955.01. The sector presents a humid tropical climate, with a height of 8 m.s.n.m., with average precipitation of 2348 mm, with a temperature of 24.7 ºC of, annual average of the last 5 years. The corn hybrid DAS 3383 was used as sowing material. The objectives were to determine the yield of corn grain with the use of nitrogen and potassium fertilizers; establish the most effective sources and doses of Nitrogen and Potassium in the increase of corn yield and perform the economic analysis of the treatments under study. The treatments used were Urea (150 kg / ha); Urea + Ammonium Sulphate (150 + 40 + 0 kg / ha); Ureas + Ammonium Sulphate (150 + 40 + 0 kg / ha); Urea + Ammonium Sulphate + Potassium Muriate (150 + 40 + 90 kg / ha); Ureas + Ammonium Sulphate + Potassium Muriate (150 + 40 + 90 kg / ha); Ammonium Sulfate + Potassium Muriate (0 + 40 + 90 kg / ha) and Control (92 kg / ha N - 90 kg / ha K), applied at 13, 25 and 35 days after sowing. The present experimental work was used the design of Complete Blocks at Random, with seven treatments and three repetitions. The data obtained were subjected to the analysis of variance to know the statistical significance. The averages of the results were compared with the Tukey test at 5% significance. From the results obtained, it was determined that the control treatment with application of 92 kg / ha N - 90 kg / ha K took time to flower and mature; the use of Ureas + Ammonium Sulphate + Muriate of Potassium with a dose of 150 + 40 + 90 kg / ha was the treatment that achieved the highest height of the plant and height of insertion of the ear; the ear diameter exceeded using Urea + Ammonium Sulphate with doses of 150 + 40 + 0 kg / ha and the ear length with the use of Ureas + Ammonium Sulphate with 150 + 40 + 0 kg / ha. The treatment that was applied Ureas + Ammonium Sulphate with doses of 150 + 40 + 0 kg / ha presented greater yield of the crop, as well as the highest net benefit was achieved by the use of Urea.